Integrating Cultural Literacy and Digital Literacy in Indonesian Language Learning to Strengthen Students' National Resilience - Syamsul Ghufron; Rudi Umar Susanto; Abdullah Zawawi (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This study aims to examine the effectiveness of integrating cultural literacy and digital literacy in Indonesian language learning to strengthen students’ national resilience. A mixed methods approach with a sequential explanatory design was employed, involving elementary school students as research subjects. Data were collected through tests, observations, interviews, and documentation, and analyzed using quantitative and qualitative techniques. The results show that the integration of cultural and digital literacy significantly improves students’ reading comprehension, as indicated by a high N-Gain score (0.71) in the experimental group compared to the control group (0.46). In addition, students’ cultural literacy and digital literacy increased, particularly in understanding cultural values, evaluating information, and using digital media responsibly. Learning engagement also improved, with students demonstrating more active, interactive, and reflective participation. Qualitative findings reveal that students better understand cultural values when learning is connected to real-life contexts, while teachers perceive this approach as more effective and creative. The study concludes that integrating cultural and digital literacy is an effective strategy to support sustainable education and strengthen students’ national resilience.